Etika Marketing Syariah - Luqman Nurhisam (IQTISHADIA Jurnal Ekonomi & Perbankan Syariah, 2017)
Marketing activities (marketing) which is the activity of distributing goods and services ranging from producers to the hands of consumers. In this case there are some fundamental questions that encompass marketing activities (marketing); ranging from what is marketed, who is marketing, to how goods and services are marketed through the activities of marketing functions such as purchase, sales, transportation, and so forth. The problem that arises then is, most of the producers/the company with the marketers (marketers) who do not consider the moral and ethical aspects of marketing the products they offer, the most important for them is how to make the products they offer acceptable and successful and control the market share. Especially if the marketer is pressed by the target company that must be achieved and the bonus will be obtained, then to achieve the target, not infrequently a marketer doing various ways, to the point of crashing the signs and ethics that have been established in religion. This study aims to analyze how the ethical aspect in the concept and practice in marketing (marketing) sharia by the company / producer of goods and services. The research method used in this research is descriptive qualitative analysis, using linguistic or language approach that is describe the concept and structure of marketing language as it is. From this study it can be concluded that the majority of scholars allow the concepts and practices in sharia marketing, seen from the process of creation, the process of bidding, as well as the process of change of value (value) in sharia marketing there should be no things that conflict with the principles that exist in sharia. As long as it can be guaranteed, and deviation of principles in sharia does not occur in any transaction inside marketing, it can be allowed in syarak. As well as in the ethical aspect has also fulfilled the spiritual elements that are spiritual based, the divinity is sourced from the teachings of revelation as known by Islamic shari'ah (al-Qur'an and as-Sunnah).